FAKTOR PREDIKTOR YANG MEMPENGARUHI KEPATUHAN MINUM OBAT PADA PENDERITA HIPERTENSI DI INDONESIA - Wahyu Puspitasari; Yati Afiyanti; Ida Farida (Nusantara Hasana Journal, 2021)
The incidence of hypertension is still one of the highest health problems in the health sector in Indonesia and around the world. Hypertension is often referred to as "The Silent Killer" and is still the third cause of death in Indonesia. Methods: This study Janis using study design Associative with engineering approaches is Cross-sectional. The sampling technique used was total sampling where all respondents who were included in this research researcher were used as samples of this study using 400 respondents. The data analysis used was univariate analysis, bivariate analysis using Chi-Square and multivariate analysis using multiple logistic regression analysis. Results: the study showed that adherence to taking medication which was dominant from low adherence was 67.8% with the results of the analysis Chi-Square of family support (p = 0000 <α = 0.05), the role of health workers (p-value=0,000 <α = 0,05), motivation for treatment (p-value=0,000 <α = 0,05). The results of multiple logistic regression analysis, there are several variables that have a significant value, namely family support (p-value=000 <α = 0,05) OR = 5,392, the role of health workers (p-value=0,000 <α = 0,05) OR = 7,798, motivation for treatment (p-value=0,000 <α = 0,05) OR = 11,027. The conclusion for this study is that there is an influence between family support, the role of health workers and treatment motivation on medication adherence to hypertension sufferers in Indonesia.